2021
DOI: 10.1126/sciadv.abe3401
|View full text |Cite
|
Sign up to set email alerts
|

Ciliopathy protein HYLS1 coordinates the biogenesis and signaling of primary cilia by activating the ciliary lipid kinase PIPKIγ

Abstract: Mutation of ciliopathy protein HYLS1 causes the perinatal lethal hydrolethalus syndrome (HLS), yet the underlying molecular etiology and pathogenesis remain elusive. Here, we reveal unexpected mechanistic insights into the role of mammalian HYLS1 in regulating primary cilia. HYLS1 is recruited to the ciliary base via a direct interaction with the type Iγ phosphatidylinositol 4-phosphate [PI(4)P] 5-kinase (PIPKIγ). HYLS1 activates PIPKIγ by interrupting the autoinhibitory dimerization of PIPKIγ, which thereby e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Both HYLS1 and PMM2 have not been implicated in GWAS (Table S26), but their neural-cardiac roles are relevant to schizophrenia. HYLS1 encodes hydrolethalus syndrome protein 1, which regulates the biogenesis and signaling of cilia 57 . Cilia are antenna-like organelles with essential roles in cerebral cortical 58 and cardiac 59 development.…”
Section: Resultsmentioning
confidence: 99%
“…Both HYLS1 and PMM2 have not been implicated in GWAS (Table S26), but their neural-cardiac roles are relevant to schizophrenia. HYLS1 encodes hydrolethalus syndrome protein 1, which regulates the biogenesis and signaling of cilia 57 . Cilia are antenna-like organelles with essential roles in cerebral cortical 58 and cardiac 59 development.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of primary murine and cultured human cells confirmed that, as was seen in other organisms, HYLS1 deficiency led to a ciliation defect (Dammermann et al ., 2009; Wei et al ., 2016; Hou et al ., 2020; Chen et al ., 2021; Serwas et al ., 2017). Importantly, U-ExM analysis revealed that HYLS1 mutation or HYLS1 loss leads to centrioles that are short or broken at their distal end, consistent with a weakened microtubule wall.…”
Section: Discussionmentioning
confidence: 99%
“…HLS is caused by a D211G point mutation in the conserved centriole protein HYLS1 and is enriched in the Finnish population (Mee et al ., 2005; Honkala et al ., 2009). HYLS1 is required to anchor basal bodies at the plasma membrane and assemble the transition zone required for cilia biogenesis and signaling, and recent work has implicated cilia dysfunction as the major cause of HLS defects (Dammermann et al ., 2009; Wei et al ., 2016; Serwas et al ., 2017; Hou et al ., 2020; Chen et al ., 2021). HYLS1 has been shown to be dispensable for centriole duplication and centrosome function in C. elegans, suggesting a basal body specific function (Dammermann et al ., 2009; Serwas et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Upon serum starvation, the phosphatidylinositol 5-phosphatase (INPP5E) departs from the centrosome causing depletion of PtdIns(4)P by the activity of phosphatidylinositol(4)P 5-kinase (PIPKIγ) thus freeing CEP164 for the binding with TTBK2 (Wang and Dynlacht, 2018). Furthermore, PIPKIγ recruits HYLS1 (hydrolethalus syndrome protein 1) to the ciliary base, which in turn causes activation of PIPKIγ, depletion of centrosomal PI(4)P, and axoneme extension (Chen et al, 2021). HYLS1 has been shown to play an essential role in cilia formation (Dammermann et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…TTBK2 binds to CEP164 at the DAs, which is regulated by the phosphatidylinositol(4)P 5-kinase (PIPKIγ)-mediated depletion of phosphatidylinositol-4-phosphate (PtdIns(4)P) levels at the centrosome/ciliary base (Xu et al, 2016; Wang and Dynlacht, 2018). PIPKIγ, furthermore, interacts and recruits HYLS1 (hydrolethalus syndrome protein 1) to the ciliary base causing activation of PIPKIγ and in turn accelerated depletion of centrosomal PI(4)P and axoneme extension (Dammermann et al, 2009; Chen et al, 2021). In addition to TTBK2, the microtubule (MT)-associated protein/MT affinity regulating kinase 4 (MARK4) is required for the initiation of axoneme extension (Kuhns et al, 2013).…”
Section: Introductionmentioning
confidence: 99%